RP-HPLC Method Development and Validation for Simultaneous Estimation of Clobetasol Propionate and Fusidic Acid in Cream: - (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A simple, rapid, precise, and accurate high-performance liquid chromatography method was developed for simultaneous estimation of Clobetasol propionate and Fusidic acid in cream. The separation was obtained using a mobile phase consisting of Acetonitrile and Water in the ratio of 90:10 and adjusting pH 5.0 with Glacial acetic acid (10%) using Shim-pack solar C18 (250 × 4.6 mm, 5 μm) column. The flow rate of 1.0 mL/min and UV detection at 240 nm was employed. The retention time for Clobetasol propionate and Fusidic acid was 4.787 min and 6.006 min respectively. Linearity for Clobetasol propionate and Fusidic acid was found to be in the range of 3-7 μg/mL and 120-280 μg/mL, respectively. The method was validated as per the ICH guidelines and the results were within the acceptance criteria for precision, linearity, specificity, and robustness.